Longitud, peso y sexo del dorado Coryphaena hippurus (Perciformes: Coryphaenidae), del litoral de Sinaloa, Nayarit y Baja California Sur, México - Madrid, J V; Beltrán-Pimienta, R (Revista de Biología Tropical, 2001)
Dolphin fish population data were recorded from landings in Sinaloa, Nayarit and Baja Califonia Sur, Mexico, in 1997. Of 3 211 organisms, only 2 812 produced complete biometric data. The maximal length and weight were 192 cm and 30 kg. The three sampling sites and the climatic periods also were associated with different size (P < 0.05). The covariate analysis of weight and length relationships indicated significative differences (P < 0.05) for total data and by sex. Condition factor was higher throughout the study period in Mazatlán, and the variation was higher, in the spring. The sexual ratio was in Mazatlán constant, while there were more males in Nayarit in the fall and the spring and in Los Cabos in the spring. There may be population differences, between the central mexican Pacific Coast and the Peninsula of Baja data